Analysis and evaluation of tourism e-commerce websites in China. (8th January 2008) - Lu, Yaobin; Deng, Zhaohua; Wang, Bin
Internet has become a platform for companies in the travel and tourism industry to bring their products and services to the customers around the world in a direct, efficient, and cost-minimising fashion. In this research, we develop an index system for the evaluation of Chinese tourism websites, incorporating factors relating to website design, contents, and effectiveness. We use the Analytical Hierarchy Process (AHP) to determine the weights of different components of the index, and the Fuzzy Synthetic Evaluation (FSE) method to evaluate the websites. We illustrate the use of our method by analysing the China Travel Network website.